2022
DOI: 10.3390/healthcare10081464
|View full text |Cite
|
Sign up to set email alerts
|

The Radiographic Assessment of Furcation Area in Maxillary and Mandibular First Molars while Considering the New Classification of Periodontal Disease

Abstract: This study aimed to evaluate the radiographic reliability in the diagnosis of furcation involvement in first molars. A total of 52 subjects were included in the current study. Personal history regarding smoking was recorded and a periodontal examination was performed. Pocket depth (PD), clinical attachment level (CAL), gingival recession, and furcation involvement in all first molars were assessed for each patient. Periodontal staging and grading were evaluated using the new classification of periodontal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…These findings are consistent with those of some previous studies that have also reported discrepancies between clinical and radiographic measurements of FI [3,4]. However, it should be noted that the current study focused on a specific type of radiographic examination through CBCT, whereas previous studies used different types of radiographic measurements, such as periapical and panoramic radiographs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those of some previous studies that have also reported discrepancies between clinical and radiographic measurements of FI [3,4]. However, it should be noted that the current study focused on a specific type of radiographic examination through CBCT, whereas previous studies used different types of radiographic measurements, such as periapical and panoramic radiographs.…”
Section: Discussionsupporting
confidence: 92%
“…Hamp's and Glickman's classification systems are used to categorize FI based on horizontal bone loss at the furcation area [3,4]. While the accuracy of clinical detection largely depends on an operator's skills, which can differ from one operator to another, the measurements are often based on the penetration depth into inflamed connective tissues rather than the actual depth of the interradicular bony defect [5].…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic diagnosis is the most widely used and important means of evaluating teeth in dentistry. The use of new X-ray techniques like cone beam-computed tomography (CBCT) and magnetic resonance imaging (MRI) has the potential to enhance the accuracy of diagnosing root canal bifurcations [14]. This means that clinical dentists still mostly rely on traditional X-ray images.…”
Section: Introductionmentioning
confidence: 99%